The Formation Of Adjectives From Nouns In English Through Suffixation: A Qualitative Review - islamiah, samratul (Journal of English Education, Literature and Linguistics, 2025)
The process of creating adjectives in English by adding suffixes to nouns was reviewed qualitatively in this study. Finding the morphological patterns, the difficulties students encounter, and the educational ramifications of employing these derivative suffixes are the primary goals. Through a survey of numerous scholarly works, the study demonstrates the high productivity of suffixes like -ful, -less, -ous, -ic, -al, and -y in enhancing English vocabulary. However, a lack of knowledge of morphological principles sometimes hinders their proper usage, resulting in a number of typical mistakes, including misspellings, phonological faults, and mismatches. The results highlight how crucial it is for students to have a thorough understanding of morphological patterns in order to recognize, use, and steer clear of mistakes when creating new words. It is anticipated that the findings of this study will aid in the creation of more potent teaching resources and methods for English language learners.